The Use of Hallo Application as Supporting Teaching Media in Enhancing Students` Speaking Skill - Muhammad Saiful Huda; Jusriati Jusriati; Husnani Aliah (Institut Agama Islam Negeri Palopo, 2023)
This research was aimed in increasing students` speaking skill by using Hallo Application based on android smartphone which the students able to use it everywhere. The research used pre-experimental design which used one group pre-test and post-test. The research was planned by using of hallo application as instrument and learning support. In implementation, the researcher made planning, treatment, evaluating and reflecting in every meeting. The result of this research from paired sample test showed the result of the analytical comparisons using t-test. The output shows the average before and after the test (-20,900), standard deviation (4,773), mean standard error (0,871). The bottom difference (-22.682), while the top difference (-19,117). The result of the t test = (-23,983) with a df of 29 and a significance of 0,000. Mean score were higher after teaching using Hallo Application. This means that Ha is accepted and Ho is rejected. In conclusion, the use of Hallo Application is an effective strategy that will use to teach class XI of Senior High School Students.